Dissolved organic matter and microbial carbon of Protocalcic Chernozems of different land management - V. A. Kholodov; Yu. R. Farkhodov; N. V. Yaroslavtseva; N. N. Danchenko; B. S. Ilyin; V. I. Lazarev (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
Water-extractable organic matter is the most active and mobile form of soil carbon. The other active fraction and extremely biolabile is the carbon constituent of microorganisms. Both of these fractions play an essential role in agrocenoses and in the global carbon cycle on our planet. The aim of the work was to estimate the carbon content of water-extractable organic matter as well as that of microbial origin in typical chernozems (Protocalcic Chernozems) of different land-use types. Protocalcic Chernozem samples taken from the fields of long-term experiments with different types of land use were investigated: a permanent bare fallow for 55 years (since 1964); conventional tillage – four-field crop rotation, first rotation; direct seeding – crop rotation similar to direct seeding, first rotation; a 21-year fallow (since 1998) after 34 years of bare fallow (since 1964). We determined the carbon content of water-extractable organic matter and the carbon content of microbial origin. In the studied series of variants, the proportion of carbon of water-extractable organic matter in the total amount of organic matter in the upper horizon (0–15 cm) was 0.69, 0.85, 1.01, and 0.98%, respectively, while that of carbon of microbial origin was 0.27, 0.55, 0.53, and 1.52%. It was noted that against the background of increasing the content of total organic carbon in direct seeding variant, compared with the traditional soil treatment, the microbial biomass in this variant does not increase. The fallow variant, unlike all other types of land use, is characterized by a higher proportion of microbial carbon, in contrast to the carbon of water-extractable organic matter.